CHARACTER ASSOCIATION AND PATH ANALYSIS FOR YIELD ATTRIBUTES IN PIGEONPEA (Cajanus cajan (L.) Millsp. - V. JAYALAKSHMI (The Journal of Research ANGRAU, 2018)
Character associations and path coefficients among 47 pigeonpea genotypes were studied during kharif, 2013 for seed yield and yield components.The results revealed that phenotypic and genotypic correlations are in similar direction and significant. Seed yield plant-1 was observed to be significantly and positively associated with days to maturity, plant height, no. of primary branches plant-1, no. of secondary branches plant-1 and no. of pods plant-1. The studies on path coefficients revealed high and positive direct effects of no. of pods plant-1, no. of secondary branches plant-1 and no. of primary branches plant-1 at both phenotypic and genotypic levels on seed yield, indicating the importance of direct selection for these traits in pigeonpea yield improvement programmes.